Truth and Writing in Daniel: Memories of Persian Media: Ancient Jewish Memories of Achaemenid Persia 1 - Carlson Hasler, Laura; Nati, James (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2025)
This essay explores how the book of Daniel articulates a contrast between Babylonian and Persian media. While Daniel 1–5 imagines Babylonian power as linked to monumentality, Daniel 9–12, set in the reigns of Darius and Cyrus, emphasizes circulatable writing as crucial to order and truth. This contrast is mobilized by the book’s authors to depict the Seleucids as akin to the Neo-Babylonians and in contrast to the Persians. This contrast is achieved via the book’s language of written “truth” (אמת).